2021
DOI: 10.1017/hpl.2021.57
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of micrometre-sized periodic gratings in free-standing metallic foils for laser–plasma experiments

Abstract: Engineered targets are expected to play a key role in the future high-power laser experiments calling for a joined, extensive knowledge in materials properties, engineering techniques, and plasma physics. In this work, we propose a novel patterning procedure of self-supported 10 µm thick Au and Cu foils for obtaining periodic micron-size gratings as targets for high-power laser applications. Accessible techniques were considered, by using cold rolling, electron beam lithography, and Arion milling process. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 62 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…[78,79] To comprehend the absorption mechanism, the equivalent circuit theory has been broadly utilized. [80][81][82][83][84] Representing periodic patterns through the resistance-inductance-capacitance (RLC) circuit model, where the equivalent impedance (Z u ) can be described in Equation (1) [85][86][87]…”
Section: Design Principles and Methods Of Absorbersmentioning
confidence: 99%
See 1 more Smart Citation
“…[78,79] To comprehend the absorption mechanism, the equivalent circuit theory has been broadly utilized. [80][81][82][83][84] Representing periodic patterns through the resistance-inductance-capacitance (RLC) circuit model, where the equivalent impedance (Z u ) can be described in Equation (1) [85][86][87]…”
Section: Design Principles and Methods Of Absorbersmentioning
confidence: 99%
“…[ 78,79 ] To comprehend the absorption mechanism, the equivalent circuit theory has been broadly utilized. [ 80–84 ] Representing periodic patterns through the resistance–inductance–capacitance (RLC) circuit model, where the equivalent impedance (Zu$Z_{\text{u}}$) can be described in Equation () [ 85–87 ] Zu=R+jωL+1jωC$$\textrm{ } Z_{\text{u}} = R + j \omega L + \frac{1}{j \omega C}$$where R , C , and L are the equivalent resistance, capacitance, and inductance of periodic patterns, respectively. For dielectric spacers supported by a grounding plane, the equivalent impedance (Zt$Z_{t}$) is expressed as [ 88 ] Zt=jZ0μrεrtan(ωtμ0ε0μrεr)$$Z_{t} = j Z_{0} \sqrt{\frac{\left(\mu\right)_{r}}{\left(\epsilon\right)_{r}}} tan \left(\right.…”
Section: Design and Preparation Of Masmentioning
confidence: 99%
“…Currently, the processes [1]. With the advent of laser-plasma accelerators, proton beams with energies of up to 100 MeV have been experimentally produced [5] via hybrid schemes involving radiation pressure acceleration [6] and target normal sheath acceleration (TNSA) [7][8][9]. Meanwhile, other mechanisms of laserproton acceleration, such as the breakout afterburner [10,11] and collision-less shock acceleration (CSA) [12][13][14], have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recent numerical and experimental studies have shown that creating nano- and microstructures, as well as patterns on the front surface of the targets, leads to an enhanced laser energy absorption and, hence, an improved conversion efficiency from laser energy into the resulting ion beam energy [ 21 ]. A number of surface structures have been proposed to this end, such as gratings [ 22 , 23 ], nanowires [ 24 ], nanobrushes [ 25 ], carbon foam [ 26 ], nanospheres [ 27 , 28 ] or nanoparticles [ 29 ]. When used as targets in high-power laser experiments, increasing the effective surface area of thin films through the use of specific growth methods can be an effective way of improving their laser energy absorption capabilities.…”
Section: Introductionmentioning
confidence: 99%